A single-chip storage LSI for home networks. - Lim, Han-Kyu.
Network direct attached storage (NDAS) is a network storage architecture that allows direct attachment of existing ATA/ATAPI devices to Ethernet without a separate server. Unlike other architectures such as NAS, SAN, and USB mass storage, no server computer intervenes between the storage and the client hosts. We describe an NDAS disk controller (NDC) amenable to low-cost single-chip implementation that processes a simplified L3/L4 protocol and converts commands between ATA/ATAPI and Ethernet, while the remaining complex tasks are performed by remote hosts. Unlike NAS architectures that use TCP/IP, NDAS uses a TCP-like lean protocol that lends itself well to high-performance hardware realization. Thanks to the simple NDAS architecture and protocol, an NDC implemented on a single 4 mm × 4 mm chip in 0.18 μm CMOS technology achieves a maximum throughput of 55 Mbytes/s on gigabit Ethernet, which is comparable to that of a high-performance disk locally attached to a host computer.
Keywords: CMOS technology; Ethernet; TCP-like lean protocol; disk controller; home network; network direct attached storage; single-chip storage LSI